2023
DOI: 10.3390/biom13081215
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of the Copper Nitrite Reductase from Neisseria gonorrhoeae

Abstract: The copper-containing nitrite reductase from Neisseria gonorrhoeae has been shown to play a critical role in the infection mechanism of this microorganism by producing NO and abolishing epithelial exfoliation. This enzyme is a trimer with a type 1 copper center per subunit and a type 2 copper center in the subunits interface, with the latter being the catalytic site. The two centers were characterized for the first time by EPR and CD spectroscopy, showing that the type 1 copper center has a high rhombicity due… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
2
1
2
Order By: Relevance
“…The unfolding temperature observed at pH 7.0 is relatively higher than that observed for other proteins isolated from mesophilic bacteria (Nobrega et al, 2017), although some exceptions have been reported (Barreiro et al, 2023b). However, the T M is relatively low (90 °C, at pH 5.0) compared to that of cytochrome c 552 from thermophilic organisms: Hydrogenophilus thermoluteolus and H. thermophilus, which have a T M of 108 °C and 121 °C, respectively, at pH 5.0 (Oikawa et al, 2005;Nakamura et al, 2006).…”
Section: Thermostabilitycontrasting
confidence: 57%
“…The unfolding temperature observed at pH 7.0 is relatively higher than that observed for other proteins isolated from mesophilic bacteria (Nobrega et al, 2017), although some exceptions have been reported (Barreiro et al, 2023b). However, the T M is relatively low (90 °C, at pH 5.0) compared to that of cytochrome c 552 from thermophilic organisms: Hydrogenophilus thermoluteolus and H. thermophilus, which have a T M of 108 °C and 121 °C, respectively, at pH 5.0 (Oikawa et al, 2005;Nakamura et al, 2006).…”
Section: Thermostabilitycontrasting
confidence: 57%
“…The unfolding temperature observed at pH 7.0 is relatively higher than that observed for other proteins isolated from mesophilic bacteria (Nobrega et al, 2017), although some exceptions have been reported (Barreiro et al, 2023b). However, the TM is relatively low (90 ºC, at pH 5.0) compared to that of cytochromes c552 from thermophilic organisms: Hydrogenophilus thermoluteolus and H. thermophilus, which have a TM of 108 º C and 121 ºC, respectively, at pH 5.0 (Oikawa et al, 2005;Nakamura et al, 2006).…”
Section: Thermostabilitymentioning
confidence: 69%
“…Estes domínios adicionais ligam hemos do tipo-c ou centros CuT1 e medeiam a transferência de eletrões para o domínio conservado [23]. O domínio conservado nas várias famílias de CuNiR tem uma estrutura homotrimérica (Figura 3C), com cada subunidade contendo os dois centros mononucleares de cobre [17,24]. O centro CuT1 é coordenado por dois resíduos de histidina, uma metionina e uma cisteína, da mesma subunidade.…”
Section: Redutase Do Nitritounclassified
“…Por sua vez, o centro CuT2 está localizado na interface entre dois monómeros e é coordenado por três cadeias laterais de histidina, uma das quais é do monómero adjacente (Figura 3D) [25]. Estes dois centros estão ligados entre si por uma ponte de cisteína-histidina conservada que consiste na cisteína que coordena o centro CuT1 e na histidina que coordena o centro CuT2 [17,23,24].…”
Section: Redutase Do Nitritounclassified

Elogio da Desnitrificação

Isabel Moura,
Sofia R. Pauleta,
Marta S. P. Carepo
et al. 2024
BSPQuimica